Nomograms for predicting adverse obstetric outcome in IVF pregnancy: A preliminary study. Issue 2 (2nd February 2021) - Portal, Alice; Sunyach, Claire; Loundou, Anderson; Lacroix‐Paulmye, Odile; Perrin, Jeanne; Courbiere, Blandline
Abstract: Background: In a previous study, we showed that the obstetric complication rate after in vitro fertilization (IVF) pregnancy was 40%. The main objective of our study was to determine maternal prognosis factors that influence the IVF pregnancy outcome. Methods: We conducted an observational retrospective monocentric study between January 2014 and January 2018. Pregnancy over 22 gestational weeks (GW) obtained after IVF in our infertility clinic was included. Maternal characteristics and pregnancy outcome were collected. Results: Data from 498 IVF pregnancies were analyzed. The most significant maternal prognosis factors for obstetric complications were maternal age above 40 years (OR 3, 0 [95% IC 1, 30‐7, 09], P  = 0, 010), twin pregnancies (3.8 [95% IC 1.49‐9.99], P  = .005), daily maternal smoking above 10 cigarettes (7.1 [95% IC 1.22‐41.74], P  = .029), maternal obesity (2.2 [95% IC 1.19‐4.07], P  = .012), endometriosis stages III and IV (6.4 [95% IC 1.52‐27.04], P  = .011), and history of ovarian hyperstimulation syndrome (OHSS) in early pregnancy (5.7 [95% IC 1.29‐24.74], P  = .021). Risk increase was independent of pregnancy type (singleton or twin) and allowed the elaboration of 2 nomograms. Conclusions: Our study showed a link between some maternal factors and increase in obstetric complications after IVF. Screening of these factors during preconceptional visit is essential to identify at high‐risk pregnancies and adapt their monitoring.